Reputation Evaluation of the Factors Regulating the Development of the Consumer Goods Market in the Region - Popadynets, Nazariy; Bondarenko, Viktoriya; Staryk, Roma; Chakii, Olha; Voitenko, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The article substantiates the essence of dysfunctions as a key phenomenon that leads to deformation or partial failure to perform functions by the subjects of the internal consumer market. The features of the influence of socio-economic factors investigated within the functioning efficiency of the regional food market. The evaluation of the influence for the food market factors in the region carried out by classifying the factors by the influence sphere and the regulation degree, assessing the influence of the food market factors on the main indicator models. These models contain indicators, despite the existing system of statistical observation in the region, studying the relationships between factors and indicators characterizing food market and identifying the results of dysfunctions. A block of socio-economic determinants of realizing the potential of the consumer (food) market in the region is proposed. Correlation analysis of factors affecting the food market and the volume of products sold (agriculture, food production, beverages) has been carried out. The authors built a system of correlation between the socio-economic factors of the food market and the export of agricultural products and the food industry in the region. A system of interrelation of socio-economic factors and their influence on the wholesale turnover of food products in the region proposed, as well as a system of interrelation of socio-economic factors with the resulting "gross regional product". The nature of the emergence and the essence of dysfunctions in the regulation of the consumer market development are concretized. The consequences of state regulation dysfunctions for the development of the consumer goods internal market are determined and characterized. The main dysfunctional factors of influence on the regulators of the regional market development grouped in the aspect of competitive markets.